Desain Bahan Pembinaan Suami-Istri Kristen untuk Ketahanan Keluarga Warga Gereja - Herdiana Sihombing; Elisamark Sitopu; Herowati Sitorus; Roy Charly HP Sipahutar; Bintahan M. Harianja (IMMANUEL: Jurnal Teologi dan Pendidikan Kristen, 2020)
The high divorce rate in Indonesia, including among Christian families, has in recent years been a struggle together. Divorce itself is the mouth of a variety of pressures faced by Christian families that are not properly resolved. Not a few Christian families have a vulnerable resilience due to their inability to manage conflicts that occur. On the other hand, the Church must recognize that it has an ethical and theological responsibility to maintain the resilience of the family members of its congregation. However, the fact is that most churches do not have a programmed mission to nurture husband and wife members of their congregations in order to maintain family resilience. In fact, many churches do not have documented teaching material for cultivating Christian families. This article is a summary of development research that seeks to create a design for Christian husband and wife formation materials that can later be used by church leaders for the survival of the family of church members. The research method used is Research and Development (R D), which is used to produce certain products, and test their effectiveness. In this research, the design of Christian husband and wife guidance materials for the family resilience of church members is produced.AbstrakTingginya angka perceraian di Indonesia, tidak terkecuali di kalangan keluarga Kristen, dalam beberapa tahun terakhir telah menjadi pergumulan bersama. Perceraian sendiri merupakan muara dari beragam tekanan yang dihadapi oleh keluarga Kristen yang tidak terselesaikan dengan baik. Tidak sedikit keluarga Kristen yang memiliki ketahanan yang rentan akibat ketidakmampuan dalam mengelola konflik yang terjadi. Di lain pihak, Gereja harus menyadari bahwa ia memiliki tanggung jawab etis dan teologis untuk menjaga ketahanan keluarga anggota jemaatnya. Tetapi faktanya sebagian besar gereja tidak memiliki misi yang terprogram untuk membina suami-istri warga jemaatnya demi menjaga ketahanan keluarga. Bahkan banyak gereja tidak memiliki bahan pengajaran yang terdokumentasi untuk membina keluarga Kristen. Artikel ini merupakan rangkuman dari penelitian pengembangan yang berupaya menciptakan suatu desain bahan pembinaan suami-istri Kristen yang nantinya dapat dipakai oleh pimpinan-pimpinan gereja untuk ketahanan keluarga warga gereja. Metode penelitian yang digunakan adalah Research and Development (R D), yang digunakan untuk menghasilkan produk tertentu, dan menguji keefektifanya. Pada penelitian ini dihasilkan desain bahan pembinaan suami-istri Kristen untuk ketahanan keluarga warga gereja.